Propagule size and shape may promote local wind dispersal in freshwater zooplankton—a wind tunnel experiment. (6th October 2015) - Pinceel, Tom; Brendonck, Luc; Vanschoenwinkel, Bram
Abstract: Current evidence supports that dormant eggs of many zooplankton species from inland waters can be transported by wind. However, little is known about variation in wind dispersal propensity among different species and propagule types. Here, we experimentally investigate the wind speed required to pick‐up propagules of a wide range of freshwater zooplankton species on different substrates. Counter‐intuitively, larger propagules were consistently picked‐up at lower wind speeds than smaller propagules. Grain size of the substrate affected adhesion because propagules were more easily picked‐up from fine grained than from coarse grained or smooth surfaces. Overall, these results suggest that propagule morphology affects wind dispersal propensity and propagule bank erosion, providing a possible explanation for the large interspecific and intraspecific variation in propagule size and shape observed in nature. Ultimately, a better understanding of the link between propagule morphology, habitat structure, and dispersal propensity will be useful to understand diversity patterns and temporal dynamics in lentic aquatic habitats. It could also help to predict range expansion of freshwater zooplankton species, many of which are invasive outside of their natural ranges.